Apocalyptic, administrative and peasant memories: for a critique of the memory of sandinismo - Delgado Aburto, Leonel (Meridional. Revista Chilena de Estudios Latinoamericanos, 2014)
This article argues that the memory of the Sandinista revolution is permeated by the work of the Sandinistas ruling Nicaragua during the 1980s, and that now that memory is mixed with global liberalism. Furthermore, the Sandinista memory can be projected to a Latin American range of changes. Folloving that idea, my text analyzes Julio Cortazar’s perspective on the Sandinista revolution and the global and dystopian moment of its development. A third aspect considered is the memory the peasants as an absent element in the leading Sandinista memory.